Peranan Sosiologi Dalam Kebijakan Pemerintah Terhadap Interaksi Sosial Dan Pemberdayaan Masyarakat - Emi Handrina (LPPM Universitas Dharma Andalas, 2026)
The government is an institution that has the authority and responsibility to regulate and manage the government affairs of a country or region. The government is tasked with making policies that are in accordance with the needs and aspirations of the community, and also implementing these policies by taking concrete actions. Sociology also discusses the inequality that occurs in society related to social class, gender, ethnicity, and other factors. Sociology will also analyze various things so that patterns of injustice and discrimination that occur can be identified and explained. Then, the authorities can take solutions to this inequality. Social interaction between human groups also occurs in society. This interaction is more dominant when there is a clash between individual interests and group interests. Overcoming the problems faced, of course, many obstacles and challenges are found. However, the role of local government to bear such a great risk is not only a necessity but also how the government embraces all components of society to be included in the process of regional development and community empowerment.